All 2D WSe2/MoS2 heterojunction photodiode and its image sensor application - Ahn, Jongtae; Kang, Ji-Hoon; Park, Min-Chul; Hwang, Do Kyung (OPTICAL SOC AMER, 2020)
Two-dimensional (2D) layered van der Waals atomic crystals exhibit many fascinating properties. In particular, their dangling-bond-free nature enables different 2D materials to be stacked on the top of each other without restraint, thereby forming a heterostructure. In this study, a high-performance all 2D heterojunction photodiode with a graphene contact as an electrode is demonstrated. It exhibits an excellent electrical performance (ideality factor of 1.2 and rectification ratio of 104), a broad spectral photoresponse (from 450 to 980 nm), and a remarkable linearity with a linear dynamic range of 113 dB. Finally, a self-powered single pixel imager is demonstrated as a feasible optoelectronic application.